Record of Epibiont ciliates (Ciliophora: Peritrichia) living on freshwater invertebrates in a floodplain wetland - Kumari, Suman; Kumar, Ram; Sarkar, U. K.; Das, B. K. (Journal of the Inland Fisheries Society of India, 2022)
Ciliate epibionts associated with freshwater invertebrates, such as crustaceans and rotifers are reported to be widespread in marine but much less in freshwater aquatic ecosystems and their ecological roles are not well known. The epibionts association with invertebrates increases significant biomass in aquatic ecosystem. Aquaculture farms commonly support a high abundance of invertebrates associated with epibionts due to their hydro-ecology, however, epibionts in wetlands are meagrely studied. We investigated the occurrence of ciliate epibionts on freshwater invertebrates in a floodplain wetland of Bihar, India. Each host basibiont was infested with different densities of epibionts. The ovigerous female rotifers, copepod adult and nauplii were more infested by epibionts. Copepod adults had the highest epibiont load, followed by copepod nauplii and Keratella sp. The study, for the first time observed different intensity of epibiont infestation on different group of invertebrates in floodplain wetland, and surface morphology of the basibionts might play a significant role in this. The ecology of the hosts and the epibionts needs further research to unravel their roles in aquatic ecosystems.Key words Epibionts; Freshwater; Invertebrates; Floodplain wetland